1998
DOI: 10.1074/jbc.273.35.22311
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Fourth Ligand to the [2Fe-2S] Cluster in Animal Ferrochelatase Is a Cysteine

Abstract: The terminal enzyme in heme biosynthesis, ferrochelatase (E.C. 4.99.1.1), catalyzes the insertion of iron into protoporphyrin IX. Nuclear-encoded and produced in the cytoplasm, ferrochelatase is proteolytically processed upon translocation into the mitochondrion. In eukaryotes, the mature-length 42,000 Da protein is associated with the inner mitochondrial membrane, with the active site facing the mitochondrial matrix (1). The proposed catalytic mechanism (2) initially involves a metaldependent, enzyme-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 38 publications
(33 reference statements)
1
37
0
Order By: Relevance
“…14 The crystal structure of human ferrochelatase suggests a structural role for the Fe-S cluster by revealing a unique stabilizing bridge formed by the cluster between the 3 carboxy-terminal cysteines and a fourth internal cysteine. 12,15 Mutations in the 4 coordinating cysteine residues of recombinant human ferrochelatase resulted in an inactive enzyme, 15 . Initial demonstration of decreased ferrochelatase activity in cultured rat hepatocytes treated with S-nitroso-N-acetylpenicillamine, 19 a nitric oxide (NO)-generating compound, prompted 2 further studies, which showed that the cluster is sensitive to destruction by NO in vitro, 20 and in cultured cells.…”
Section: Introductionmentioning
confidence: 99%
“…14 The crystal structure of human ferrochelatase suggests a structural role for the Fe-S cluster by revealing a unique stabilizing bridge formed by the cluster between the 3 carboxy-terminal cysteines and a fourth internal cysteine. 12,15 Mutations in the 4 coordinating cysteine residues of recombinant human ferrochelatase resulted in an inactive enzyme, 15 . Initial demonstration of decreased ferrochelatase activity in cultured rat hepatocytes treated with S-nitroso-N-acetylpenicillamine, 19 a nitric oxide (NO)-generating compound, prompted 2 further studies, which showed that the cluster is sensitive to destruction by NO in vitro, 20 and in cultured cells.…”
Section: Introductionmentioning
confidence: 99%
“…The two domains associate to form a cleft, in which conserved residues, proposed to be critical in the binding of substrates and in the proper functioning of the enzyme, are located [5]. In contrast to the bacterial and yeast ferrochelatases, which appear to be devoid of cofactors, vertebrate and Drosophila melanogaster ferrochelatases are metalloenzymes with a [2Fe-2S] cluster [7][8][9][10]. Despite having no direct catalytic role, the iron-sulphur cluster is essential for activity of the enzyme [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite common catalytic and scaffold mechanisms shared by the NIF, ISC, and SUF systems, there are a number of differences among these systems (10); the ISC and SUF systems appear to be considerably more complex than the NIF system. For example, heat-shock-cognate (Hsc) proteins have been suggested to have chaperone-like functions in the ISC system for the formation of transient Fe-S clusters or insertion into various target proteins in bacteria and yeast (7,26,30,50,51). Our in vivo complementation study revealed that the NIF-like system does not require any additional component other than NifS and NifU for Fe-S cluster assembly under anaerobic conditions.…”
mentioning
confidence: 99%